A framework for virtual organization requirements. Issue 4 (November 2016) - Priego-Roche, Luz; Front, Agnès; Rieu, Dominique
Abstract Virtual organizations (VOs) are formed by an alliance of organizations linked by a partnership for dealing with emerging challenges. Information and communication technologies play a fundamental role facilitating cooperation, communication and collaboration among the VO members. The formal identification and representation of Requirements Engineering (RE) for one organization have been researched to a large extent along with several elicitation techniques. However, these techniques are not adequate for covering the major challenges of RE for VO. We explore the work done in the management and RE fields to propose a model-based framework for eliciting VOs' requirements. The goal is to analyze the VO from two points of view: border (intra-organizational, inter-organizational and extra-organizational) and abstract (intentional, organizational and operational). This article includes the framework validation with a case study and a transformation process to develop partial Business Process Diagram from the intentional models.